2013
DOI: 10.4236/jep.2013.47a004
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Non-Point Pollution Loads in the Lake Uluabat Basin

Abstract: Lake Uluabat, having an international significance and subject to the Ramsar Convention, is fed by the basin of Mustafakemalpaşa Stream which runs through fertile lands utilized for livestock breeding and agriculture. In this study, total amount of nitrogen (TN) and phosphorus (TP) loads of non-point pollutants (agriculture, livestock breeding, vegetation, surface runoff and small settlements) was calculated. It was found out that most intensive pollution load stemmed from livestock breeding which causes dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The data are the average of all sampling stations for all seasons and the order of concentrations is Fe > Mn > Ni > Zn > Cr > Pb > Cu. It was previously investigated and found that the main reason for heavy metal pollution in the sediment was industrial wastewater discharge and the use of agricultural pesticides in the Lake Uluabat basin (Scientific and Technical Research Council of Turkey, 2011; Katip et al, 2012a;Katip and Karaer, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The data are the average of all sampling stations for all seasons and the order of concentrations is Fe > Mn > Ni > Zn > Cr > Pb > Cu. It was previously investigated and found that the main reason for heavy metal pollution in the sediment was industrial wastewater discharge and the use of agricultural pesticides in the Lake Uluabat basin (Scientific and Technical Research Council of Turkey, 2011; Katip et al, 2012a;Katip and Karaer, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…According to the equation (1), TN, TP and COD generation loads of LPB were estimated in each unit in Table VI (column 2). The total generation loads of TN, TP, and COD was 421860.34 t, 73183.22 t and 7192384.64 t, respectively.…”
Section: A Pollutant Generation Loads Of Lpbmentioning
confidence: 99%
“…For its pollution control, estimation and evaluation studies on LPB non-point source pollution load have been the basic work. In the study area, a lot of methods can be used, for example transport coefficient model [1], SWAT [2], inventory method [3] and export coefficient model [4]. In all methods, export coefficient model was regarded as a simple and convenient model and had been applied in many areas.…”
Section: Introductionmentioning
confidence: 99%